Treatment of Severe Venous Thrombo-Embolism with Intravenous Hirudin (HBW 023): An Open Pilot Study - Parent, Florence; Bridey, Françoise; Dreyfus, Marie; Musset, Dominique; Grimon, Gilles; Duroux, Pierre; Meyer, Dominique; Simonneau, Gérald (Thrombosis and Haemostasis, 1993)
Recombinant Hirudin (rH) is an anticoagulant agent with a specific antithrombin activity independent of antithrombin III. We report the results of the first open pilot study on the curative treatment of acute venous thrombo-embolism (VTE) with rH (HBW 023) in ten patients. The dose of rH tested was 0.07 mg/kg (i.v. bolus) followed by 0.05 mg kg-1 h-1 (i.v. infusion) for 5 days, without activated partial thromboplastin time (APTT) adjustment. Within the trial, no death, VTE recurrence or major bleeding was observed; lung scan pulmonary vascular obstruction improved from 44 to 37%, whereas the venographic Marder score was unchanged; APTT ratio ranged between 1.2 and 2.8. The dose of rH assessed in this study seems to be safe and efficient in the treatment of acute VTE.